إختبار قانون فاجنر في مقابل الفرضية الكينزية في ظل وجود تغيرات هيكلية في الجزائر: Testing Wagner’s law vesrsus Keynesian hypothesis in the presence of structural changes in Algeria - جميل عبد الجليل; عكريش كمال (Journal of North African Economies, 2025)
The aim of this paper is to test the validity of Wagner’s Law versus keynesian hypothesis in Algeria from 1962-2016 by taking into account the effect of the structural changes. To this end, we use ARDL bounds testing approach to cointegration and VECM Granger causality test. The results indicate the existence of cointegration between the variables in presence of structural changes and a lack of cointegration relationship in the presence of structural changes.The findings further demonstrate income –elasticity is greater than unity whereas the VECM Granger causality test indicates the existence of unidirectional causality from GDP to government consumption spending in both long and short term. Thus, these results support the validity of Wagner’s Law in long term. The validity of Wagner’s Law against keynesian hypothesis implies that the fiscal policy in Algeria is subject to rising income and is not a mere tool to achieving growth.